Multiphase Fluid Flow through Porous Media: Conductivity and Geomechanics - MAHABADI, NARIMAN (Author); Jang, Jaewon (Advisor); Zapata, Claudia (Committee member); Kavazanjian, Edward (Committee member); Arizona State University (Publisher) (2016)
abstract: The understanding of multiphase fluid flow in porous media is of great importance in many fields such as enhanced oil recovery, hydrology, CO2 sequestration, contaminants cleanup, and natural gas production from hydrate bearing sediments. In this study, first, the water retention curve (WRC) and relative permeability in hydrate bearing sediments are explored to obtain fitting parameters for semi-empirical equations. Second, immiscible fluid invasion into porous media is investigated to identify fluid displacement pattern and displacement efficiency that are affected by pore size distribution and connectivity. Finally, fluid flow through granular media is studied to obtain fluid-particle interaction. This study utilizes the combined techniques of discrete element method simulation, micro-focus X-ray computed tomography (CT), pore-network model simulation algorithms for gas invasion, gas expansion, and relative permeability calculation, transparent micromodels, and water retention curve measurement equipment modified for hydrate-bearing sediments. In addition, a photoelastic disk set-up is fabricated and the image processing technique to correlate the force chain to the applied contact forces is developed. The results show that the gas entry pressure and the capillary pressure increase with increasing hydrate saturation. Fitting parameters are suggested for different hydrate saturation conditions and morphologies. And, a new model for immiscible fluid invasion and displacement is suggested in which the boundaries of displacement patterns depend on the pore size distribution and connectivity. Finally, the fluid-particle interaction study shows that the fluid flow increases the contact forces between photoelastic disks in parallel direction with the fluid flow. Dissertation/Thesis Doctoral Dissertation Civil and Environmental Engineering 2016